Fgf9 and Wnt4 act as antagonistic signals to regulate mammalian sex determination. - Yuna Kim; Akio Kobayashi; Ryohei Sekido; Leo DiNapoli; Jennifer Brennan; Marie-Christine Chaboissier; Francis Poulat; Richard R Behringer; Robin Lovell-Badge; Blanche Capel (PLoS Biology, 2006)
The genes encoding members of the wingless-related MMTV integration site (WNT) and fibroblast growth factor (FGF) families coordinate growth, morphogenesis, and differentiation in many fields of cells during development. In the mouse, Fgf9 and Wnt4 are expressed in gonads of both sexes prior to sex determination. Loss of Fgf9 leads to XY sex reversal, whereas loss of Wnt4 results in partial testis development in XX gonads. However, the relationship between these signals and the male sex-determining gene, Sry, was unknown. We show through gain- and loss-of-function experiments that fibroblast growth factor 9 (FGF9) and WNT4 act as opposing signals to regulate sex determination. In the mouse XY gonad, Sry normally initiates a feed-forward loop between Sox9 and Fgf9, which up-regulates Fgf9 and represses Wnt4 to establish the testis pathway. Surprisingly, loss of Wnt4 in XX gonads is sufficient to up-regulate Fgf9 and Sox9 in the absence of Sry. These data suggest that the fate of the gonad is controlled by antagonism between Fgf9 and Wnt4. The role of the male sex-determining switch--Sry in the case of mammals--is to tip the balance between these underlying patterning signals. In principle, sex determination in other vertebrates may operate through any switch that introduces an imbalance between these two signaling pathways.